2023
DOI: 10.1158/1535-7163.mct-22-0583
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Combination Olaparib and Radium-223 in Men with Metastatic Castration-Resistant Prostate Cancer (mCRPC) with Bone Metastases (COMRADE)

Abstract: Given that radium-223 is a radiopharmaceutical that induces DNA damage, and olaparib is a PARP inhibitor that interferes with DNA repair mechanisms, we hypothesized their synergy in mCRPC. We sought to demonstrate the safety and efficacy of olaparib + radium-223. We conducted a multicenter phase 1 3+3 dose escalation study of olaparib with fixed dose radium-223 in patients with mCRPC with bone metastases. The primary objective was to establish the RP2D of olaparib, with secondary objectives of safety, PSA resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Initial phase I data published noted that the recommended dose of olaparib was reduced to 200mg twice daily as compared to the typical dosing used in monotherapy due to anemia and thrombocytopenia observed at higher doses ( 54 ). Updated phase I results from this study reported that of 12 patients enrolled, all patients had received prior ARSI therapy, and 3 patients received prior docetaxel ( 55 ). Dose limiting toxicities included cytopenias, fatigue, and nausea.…”
Section: Parpi Combination Strategiesmentioning
confidence: 99%
“…Initial phase I data published noted that the recommended dose of olaparib was reduced to 200mg twice daily as compared to the typical dosing used in monotherapy due to anemia and thrombocytopenia observed at higher doses ( 54 ). Updated phase I results from this study reported that of 12 patients enrolled, all patients had received prior ARSI therapy, and 3 patients received prior docetaxel ( 55 ). Dose limiting toxicities included cytopenias, fatigue, and nausea.…”
Section: Parpi Combination Strategiesmentioning
confidence: 99%
“…Bone metastases from various cancers are a major cause of morbidity, severe pain, and mobility difficulties. The mechanisms of bone metastasis are many, and the current treatments vary. Radionuclide treatment using Ra-223 (Xofigo) for bone pain has been approved by the FDA, providing a novel treatment to patients with castration-resistant prostate cancer with symptomatic bone metastases . It would be reasonable to assume that bone metastasis of the PSMA tumor might not be a uniform process during the progression of prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of beta particle therapies, with PARPi, like Olaparib, has been a subject of research interest 82 , 83 . A recent phase I study specifically investigated the safety profile of combining Olaparib with 223 Ra in patients with mCRPC, indicating the growing interest and exploration of this combination in clinical settings 84 .…”
Section: Current and Future Combination Therapy Approaches In Pca Tre...mentioning
confidence: 99%